THE INFLUENCE OF INFRASTRUCTURE, POVERTY AND INCOME ON FOOD SECURITY IN SOUTH SUMATRA PROVINCE - Siti Rohima (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
This study aims to determine the influence of infrastructure, poverty and income per capita on food security in districts / cities in South Sumatra Province. The data that has been used in this study are primary and secondary data in the form of data panels in the period 2010 to 2016 with 15 district/city. The method used in the study is a quantitative method with multiple linear regression analysis. The results show that infrastructure, poverty and income per capita significantly influence food security. Meanwhile, per capita income has a large influence on food security compared to poverty and infrastructure in the district / city in South Sumatra Province.JEL Classdification: I30, I31, I38Keywords: Food Security, Income, Infrastructure, Poverty